2022
DOI: 10.31616/asj.2022.0445
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Radiculopathy: Focus on Factors for Better Surgical Outcomes and Operative Techniques

Abstract: For patients with cervical radiculopathy, most studies have recommended conservative treatment as the first-line treatment; however, when conventional treatment fails, surgery is considered. A better understanding of the prognosis of cervical radiculopathy is essential to provide accurate information to the patients. If the patients complain of persistent and recurrent arm pain/numbness not respond to conservative treatment, or exhibit neurologic deficits, surgery is performed using anterior or posterior appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 136 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…The incidence of C5 palsy was even higher in some studies: 28.9% after posterior laminectomy and fusion in the study reported by Blizzard et al [ 3 , 44 ] and 36.4% after combination surgery in the study by Chang et al [ 45 ]. Although our C5 palsy rates were low, we surmise that the occurrence of this complication may be related to the severity of the foraminal stenosis or the duration of preoperative symptoms, as we used a combined approach in patients with severe stenosis to preserve the foramen height for better foramen decompression, as has been performed in previous studies [ 42 , 46 ]. Thus, it may be impossible to eliminate C5 palsy.…”
Section: Discussionmentioning
confidence: 90%
“…The incidence of C5 palsy was even higher in some studies: 28.9% after posterior laminectomy and fusion in the study reported by Blizzard et al [ 3 , 44 ] and 36.4% after combination surgery in the study by Chang et al [ 45 ]. Although our C5 palsy rates were low, we surmise that the occurrence of this complication may be related to the severity of the foraminal stenosis or the duration of preoperative symptoms, as we used a combined approach in patients with severe stenosis to preserve the foramen height for better foramen decompression, as has been performed in previous studies [ 42 , 46 ]. Thus, it may be impossible to eliminate C5 palsy.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, attention should be paid to the exposure of the facial and hypoglossal nerves, branches of the external carotid, contents of the carotid sheath, and superior laryngeal nerve, and evaluation after surgery is required 23 . In addition, adjacent segment disease should be considered a common and decisive disadvantage of ACDF 24 . The surgical outcomes of various techniques for severe cord compression behind C2 body were demonstrated in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, adjacent segment disease should be considered a common and decisive disadvantage of ACDF. 24 The surgical outcomes of various techniques for severe cord compression behind C2 body were demonstrated in Table 3.…”
Section: Preservation Of C2 Muscle Attachmentmentioning
confidence: 99%
“…In this study, we selected patients who had undergone cervical decompression and fusion by the combined anterior-posterior approach as study objects. Our institution considered the combined approach for patients with certain indications based on previous studies [5,[20][21][22][23]. Those indications contained cervical myelopathy and radiculopathy with multilevel spondylosis, severe ossification of the posterior longitudinal ligament (OPLL), congenital stenosis, and multilevel fixed kyphotic deformity.…”
Section: Surgical Indication and Techniquementioning
confidence: 99%